Pengaruh Produk dan Harga Terhadap Keputusan Pembelian Konsumen dalam Pembelian Ban Mobil Pada CV. Uwais Muara Bulian - Afriantoni Afriantoni (CITRA EKONOMI, 2022)
This study aims to see product quality, and price on consumer purchasing decisions in purchasing car tires on cv. Uwais in estuary bulian. The dependent variable in this study is the decision to purchase car tires, while the independent variables are product quality and price. Data analysis was done by using multiple linear regression method with the application of t test. The aim is to find out whether product quality and price variables have a partial effect on consumer purchasing decisions. The results of the study indicate that: product quality, and price variables have a partial effect on consumer purchasing decisions in purchasing car tires at cv. Uwais. From the coefficient of determination, the Ajusted R Square value is 0.343 or equal to 34.3%. This figure indicates that purchasing decisions are influenced by product quality and price variables. While the remaining 65.7% is influenced by other variables that are not included in this study.